PENGARUH BAURAN PEMASARAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN STUDI KASUS PADA OUTLET HISANA FRIED CHICKEN RAJAWALI - Puan Santika Maharani; Amirudin; Mella Yunita (Jurnal Ekonomi dan Bisnis, 2025)
The purpose of this study is to determine how the marketing mix and product quality influence consumer purchasing decisions. This case study was conducted at Hisana Fried Chicken Outlet with a population and sample of 100 customers. This research method is in the form of a questionnaire and a questionnaire using a Likert scale model. To test normality, a requirement test was carried out. To analyze the data, a multiple regression method was used with a significance level of a = 0.05. The results of the study show that the Marketing Mix (X1) has a significant effect on the purchasing decisions of Hisana Fried Chicken Outlet customers with a significant value of 0.000. Meanwhile, Product Quality (X2) has a significant effect on the purchasing decisions of Hisana Fried Chicken Outlet customers with a significant value of 0.000, with a calculated t value greater than the t table (3.906 ˃ 1.67469). Based on SPSS output, we found that the marketing mix and compensation variables accounted for 36.8% of the variance in the purchasing decision variables, and other variables not included in this model accounted for 63.2% of the variance. In other words, there are additional independent variables that influence purchasing decisions.